Predictability of Northern Hemisphere Final Stratospheric Warmings and Their Surface Impacts. Issue 17 (2nd September 2019) - Butler, Amy H.; Charlton‐Perez, Andrew; Domeisen, Daniela I.V.; Simpson, Isla R.; Sjoberg, Jeremiah
Abstract: Each spring, the climatological westerly winds of the Northern Hemisphere (NH) stratospheric polar vortex turn easterly as the stratospheric equator‐to‐pole temperature gradient relaxes. The timing of this event is dictated both by the annual return of sunlight to the pole and by dynamical influences from the troposphere. Here we consider the predictability of NH final stratospheric warmings in multimodel hindcasts from the Subseasonal to Seasonal project database. We evaluate how well the Subseasonal to Seasonal prediction systems perform in capturing the timing of final warmings. We compare the predictability of early warmings (which are more strongly driven by wave forcing) and late warmings and find that late warmings are more skillfully predicted at longer lead times. Finally, we find significantly increased predictive skill of NH near‐surface temperature anomalies at Weeks 3–4 lead times following only early final warmings. Key Points: Final stratospheric warmings that occur in early spring are less predictable than those that occur in late spring The interannual variability in the timing of the final warming is well predicted more than 4 weeks in advance Early final warmings provide a source of surface climate predictive skill at Weeks 3–4 in Northern Hemisphere spring